Proteção de tomateiro a Meloidogyne incognita pelo extrato aquoso de Tagetes patula - Franzener, Gilmar (2005)
The aim of this work was evaluate the potential of the aqueous extract (EA) of Tagetes patula against Meloidogyne incognita in tomato plants. EA of flowers, leaves and roots were obtained by infusion in the proportion of 50 g of vegetable dehydrated material in 1000 mL of distilled water. EA was tested in vitro on eggs and second-stage juveniles (J2) of M. incognita without dilution and diluted 1:1, 1:2, 1:3 and 1:4 (extract:water, v/v) and in plants of tomato cv. "Kadá" cultivated in pots, without dilution and diluted 1:1. For in vivo assays, EA were sprayed in the leaves, soil or both, and weekly for eight weeks, just in the transplanting (one week before inoculation with pathogen), and together or one week after inoculation. EA of flowers, leaves and roots inhibited the hatching, the mobility, and caused mortality of J2 in vitro. Greater effect nematicide was obtained with roots extract that promoted the mortality of up to 68% of J2. In tomato plants were not obtained satisfactory results with just an application of EA, independent of the time and application forms, so much in the development of plants as in the galling and M. incognita reproduction. Weekly applications promoted increase in the plants development and inhibited the galling and the nematode population. Greater results were obtained by flower EA, following by leaves and smaller or non results with root EA. EA of flower without dilution inhibited in up to 62.2% the galling and 61.5 and 52.8% the number of J2 in the soil and eggs in the roots, respectively. Applications in the soil and in the aerial part presented similar results. These results indicate the potential of T. patula EA, maily of flowers, in tomato plants protection to M. incognita, and that, possibly, besides of nematicide or nematostatic effect, involves the enhances resistance of the plants to nematode